1993
DOI: 10.1007/bf00435224
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the medical regimen and partner's quality of life after heart transplantation

Abstract: The authors investigated 40 heart transplant recipients and their partners to determine both the partner's quality of life upon transplantation and the experiences of both patient and partner with compliance with the medical regimen. Data on sleep disturbances, social isolation, emotional reactions, depression, anxiety, partner's apprehension, social support and compliance (regarding behaviour and emotional experience) were obtained approximately 21 months after transplantation. Compared to related study group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…25,26 The current findings of high parental psychological distress may be a function of assessment performed in the perioperative period because past research has identified lower levels of psychological distress when assessments were made 1 or more years posttransplantation. 25,[27][28][29] Longitudinal prospective studies are needed to clarify the impact of time in relation to the transplantation on parental psychosocial adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The current findings of high parental psychological distress may be a function of assessment performed in the perioperative period because past research has identified lower levels of psychological distress when assessments were made 1 or more years posttransplantation. 25,[27][28][29] Longitudinal prospective studies are needed to clarify the impact of time in relation to the transplantation on parental psychosocial adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that several social factors, such as friends and family members' suggestion or behaviors (Stall et al, 1996;Foulkes, 1993), living alone (Besch et al, 1997;Morse et al, 1991), having an unstable social environment (Morse et al, 1991), caring for sick relatives (Muma et al, 1995), and being homeless (Samet et al, 1992) were associated with lower adherence. Conversely, a good relationship coupled with consistent support, particularly from a spouse or significant other (Evans et al, 1986;Somer and Tucker, 1988;Erdman et al, 1993), was associated with better adherence.…”
Section: Social/interpersonal Determinants Of Non-aherencementioning
confidence: 98%
“…Moreover, caregivers' mental health influences the care recipients' own health and well-being (Biegel et al 1991 ;Williamson & Shaffer, 2001;Burgener & Twigg, 2002). However, aside from studies of transplant caregivers' subclinical distress levels, primarily during the early aftermath of transplantation (Chowanec & Binik, 1989 ;Baumann et al 1992 ;Erdman et al 1993 ;Canning et al 1996;Foxall & Gaston-Johansson, 1996 ;Rodrigue et al 1997 ;Wicks et al 1998;Boyle et al 2000), there is little evidence regarding the prevalence and important risk factors for clinically significant psychiatric disorder in this population.…”
Section: Introductionmentioning
confidence: 99%